2023
DOI: 10.1002/advs.202304957
|View full text |Cite
|
Sign up to set email alerts
|

Customizable Scintillator of Cs3Cu2I5:2% In+@Paper for Large‐Area X‐Ray Imaging

Weiqing Chen,
Ting Wang,
Tianchi Wang
et al.

Abstract: High‐resolution X‐ray imaging is increasingly required for medical diagnosis and large‐area detection. However, the issues of scattering and optical crosstalk are limiting the spatial resolution of the indirect X‐ray imaging. In this study, a feasible and efficient strategy is proposed to in situ synthesize flexible Cs3Cu2I5:2%In+@paper as a superior scintillator film, which can be scaled up to an ultra‐large area of 4800 cm2. The as‐obtained Cs3Cu2I5:2%In+@paper performs a fascinating photoluminescence quantu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Since the discovery of X-ray by Ro ¨ntgen, X-ray has been widely applied in industrial inspection, scientific research, medical radiography and so on. [1][2][3][4] Accompanied by the development of applications, X-ray imaging has also become an enduring hot topic. 5,6 Over these years, metal halide perovskite scintillators with facile solution processability, ultrasensitive X-ray detection and high photo-luminescence quantum yield have attracted much attention, which allows excellent X-ray imaging properties, [7][8][9][10] such as CsPbBr 3 , 11 Cs 2 ZrCl 6 , 12 and Cs 2 AgBiBr 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of X-ray by Ro ¨ntgen, X-ray has been widely applied in industrial inspection, scientific research, medical radiography and so on. [1][2][3][4] Accompanied by the development of applications, X-ray imaging has also become an enduring hot topic. 5,6 Over these years, metal halide perovskite scintillators with facile solution processability, ultrasensitive X-ray detection and high photo-luminescence quantum yield have attracted much attention, which allows excellent X-ray imaging properties, [7][8][9][10] such as CsPbBr 3 , 11 Cs 2 ZrCl 6 , 12 and Cs 2 AgBiBr 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that fully attaching flexible scintillators to imaging objects is an effective approach. This method not only addresses the mentioned issues but also represents one of the advantages of flexible X-ray imaging . Moreover, compared with the rigid screen, such flexible screens also can alleviate vignetting problems which result from the uneven spatial distribution of X-ray dose generated by the point X-ray source .…”
mentioning
confidence: 99%